2014
DOI: 10.4142/jvs.2014.15.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of chicken peripheral blood mononuclear cells after infection by Newcastle disease virus

Abstract: Characteristic clinical manifestations of Newcastle disease include leukopenia and immunosuppression. Peripheral blood mononuclear cells (PBMCs) are the main targets of Newcastle disease virus (NDV) infection. To survey changes in proteomic expression in chicken PBMCs following NDV infection, PBMC proteins from 30 chickens were separated using two-dimensional electrophoresis (2-DE) and subjected to mass spectrometry analysis. Quantitative intensity analysis showed that the expression of 78 proteins increased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Hence, based on the results of this study, we propose that NDV may further interfere with the glycolysis pathway by different mechanisms that amplify the glycolysis inhibition, leading to the starvation of cancer cells. Deng et al (2014) suggested that NDV may reduce the activity of the host's glycolytic pathway by decreasing phosphoglycerate kinase (PGK) expression in the NDV-infected PBMCs. PGK is a glycolytic enzyme that plays an important role in cellular energy production, and it forms part of the glycolytic pathway (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, based on the results of this study, we propose that NDV may further interfere with the glycolysis pathway by different mechanisms that amplify the glycolysis inhibition, leading to the starvation of cancer cells. Deng et al (2014) suggested that NDV may reduce the activity of the host's glycolytic pathway by decreasing phosphoglycerate kinase (PGK) expression in the NDV-infected PBMCs. PGK is a glycolytic enzyme that plays an important role in cellular energy production, and it forms part of the glycolytic pathway (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…When synergized with chemotherapeutic agents, both NDV and 2-DG were found to increase significantly the anti-tumor activity in immunocompetent mice (Al-Shammari et al, 2011; Bénéteau et al, 2012). Moreover, both 2DG and NDV were shown to reduce the activity of the glycolytic pathway (Aft et al, 2002; Deng et al, 2014). Li et al (2015) found that the attenuated measles vaccine virus shifted the cellular metabolism to a high rate of glycolytic adaptation, which was efficiently targeted by dichloroacetate (DCA) (an inhibitor of glycolysis), leading to marked anti-tumor activity both in vitro and in vivo without any toxicity observed in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…NDV induced apoptosis via caspase-dependent and caspase-independent pathways [ 24 , 25 ]. Deng et al [ 26 ] found in a proteomic study that NDV downregulate phosphoglycerate kinase (PGK) expression in the NDV-infected chicken peripheral blood mononuclear cells (PBMCs), PGK is a glycolytic enzyme that participates in the glycolytic pathway, which suggests that NDV may restrict the infected cell glycolytic pathway. Its reported that interfering with cancer cells metabolism through glycolysis inhibition may enhance oncolytic virotherapy activity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that viruses rely on host proteins to replicate, one of the focuses of antiparamyxovirus research involves identifying host proteins involved in virus infection process. In recent years, to identify host proteins involved in the paramyxovirus infection process and to study paramyxovirus–host interactions systematically, several quantitative proteomic analyses have been performed on cells infected with different paramyxoviruses, including measles virus , Newcastle disease virus , and respiratory syncytial virus .…”
Section: Introductionmentioning
confidence: 99%